2018
DOI: 10.32828/mdj.v6i4.481
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status and Treatment Needs among Blind Children in Iraq

Abstract: Dental caries is a significant public health problem for a large segment of society. Blind people have been described as those who encounter more visual barriers to the receipt of dental care than other people. They may have greater problems accessing dental care or may be at increased risk from dental disease or its treatment.The present study was conducted to assess the caries prevalence, traumatic injuries, levels of oral hygiene and treatment need, in a group of 58 blind children aged (6-15) years. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Although the overall prevalence of dental caries was reported as higher for groups with VI, 24,26,27 some studies reported higher values in dental caries indices for children with no VI 11,23,25,28 . Regardless, no difference between groups was observed in the meta‐analyses for prevalence, DMFT, dmft, and dmfs, and only DMFS was significantly higher among individuals with VI.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Although the overall prevalence of dental caries was reported as higher for groups with VI, 24,26,27 some studies reported higher values in dental caries indices for children with no VI 11,23,25,28 . Regardless, no difference between groups was observed in the meta‐analyses for prevalence, DMFT, dmft, and dmfs, and only DMFS was significantly higher among individuals with VI.…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence of dental caries varied from 40% 25 to 84% 24 (individuals with VI) and from 11.5% 26 to 83% 21 (sighted individuals). TDI ranged from 9% 5 to 32.5% 20 and from 3.4% 11 to 8.7% 6 in children and adolescents with and without VI, respectively. Bleeding on probing varied from 0.6% 18 to 62.6% 22 in those with VI and 2.7% 18 to 55% 22 in sighted individuals.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations